Arthroscopic Versus Open Ankle Arthrodesis: A 5-Year Follow Up. (6th July 2022) - Abuhantash, Monther; Veljkovic, Andrea; Wing, Kevin; Gagne, Oliver; Qian, Hong; Wong, Hubert; Sadr, Hooman; Penner, Murray; Younger, Alastair
Abstract : Background: End-stage ankle arthritis has long been managed surgically with open ankle arthrodesis (OAA). Since the first published report in 1983, arthroscopic ankle arthrodesis (AAA) has been thought to be associated with improved patient-reported outcome measures (PROMs) and fewer complications. The purpose of the present study was to compare the long-term PROMs, major complications, and reoperations for these 2 approaches at up to 15 years of follow-up. Methods: This longitudinal cohort study included patients at our institution who underwent primary ankle arthrodesis for the treatment of end-stage arthritis. Demographic data and preoperative COFAS (Canadian Orthopaedic Foot and Ankle Society) ankle arthritis type were collected for all patients. PROMs were completed preoperatively, at 6 months, and annually thereafter to 5 years. PROMs were compared at all time points with use of a mixed-effects regression model that adjusted for preoperative variables and scores. Major complications and reoperations at the site of the ankle arthrodesis were also compared. Results: Of 1, 294 patients who were screened for inclusion, 351 who had undergone ankle arthrodesis between 2003 and 2019 were eligible for the study. Of those, 223 had undergone AAA and 128 had undergone OAA. The 2 groups were similar preoperatively with respect to demographics, but COFAS Type-4 arthritis was relatively more common in the OAA group and Type-1 arthritis was relatively more common in the AAA group. In addition, the Ankle Osteoarthritis Scale (AOS) score and Ankle Arthritis Score (AAS) were better in the AAA group. In the mixed-effects model analysis, the differences in postoperative outcome scores between the groups were not significant. The risk of revision due to malunion or nonunion was similar in both groups (6% in the AAA group, compared with 4% in the OAA group). Deep infection and wound complications did not occur in the arthroscopic group but occurred in 4% of the patients in the OAA group. Conclusions: After adjustment for baseline patient characteristics, there were no differences in PROMs between the 2 techniques. Ankle arthrodeses done arthroscopically had a similar revision rate but lower infection rate compared with those done with the open technique. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.